キョッコウ タイ ニオケル Pi ミャクドウ ト カンレン ゲンショウ d. ジキケン ナイ ノ ULF・VLF ハドウ ダイ1カイ キョクチ ニオケル デンリケン ジキ ソウゴウ カンソク シンポジウム PART 2 - 桑島, 正幸; クワシマ, マサユキ; KUWASHIMA, Masayuki (国立極地研究所, 1979)
P(論文) 第14次南極観測越冬隊ては,1973年8月29日から9月29日の期間に昭和基地(補正磁気緯度-66.7°,経度72.4°)とみすほ基地(-68.7°,72.9)において,誘導磁力計とフラックス・ゲート磁力計|を使っての地磁気2点観測を行った磁気圏サフストーム時においては,2観測点において各種のPi型磁気脈動か観測されたが,今回はそのうちてPi 2とPi (c)について報告する. Concurrent observations of the geomagnetic vaiiations by means of a fluxgate magnetometer and an induction magnetometer were carried out at Syowa (-66.7゜, 72.4° in corrected geomasnetic coordinates) and Mizuho Stations (-68.7°, 72.9°in corrected geomagnetic coordinates) in Antarctica during the period from August 29 to September 29, 1973, by the 14th Japanese Antarctic Research Expedition. In association with the substorm onset, expansion and recovery phases, various kinds of Pi pulsations were observed at the two stations. In the present paper, preliminary results of the Pi 2 and Pi (c) pulsations are reported. The Pi 2 period is closely associated with the auroral breakup position in the following way that it becomes shorter (longer) when the auroral breakup occurs at lower (higher) latitude. In association with Pi (c), the substorm associated Pc 3 are observed at Syowa and Mizuho Stations. departmental bulletin paper